Characterization of a mammalian prosencephalic functional plan - Croizier, Sophie; Chometton, Sandrine; Fellmann, Dominique; Risold, Pierre-Yves (Frontiers in Neuroanatomy, 2015)
Hypothalamic organizational concepts have greatly evolved as the primary hypothalamic pathways have been systematically investigated. In the present review, we describe how the hypothalamus arises from a molecularly heterogeneous region of the embryonic neural tube but is first differentiated as a primary neuronal cell cord (earliest mantle layer). This structure defines two axes that align onto two fundamental components: a longitudinal tractus postopticus/retinian component and a transverse supraoptic tract/olfactory component. We then discuss how these two axonal tracts guide the formation of all major tracts that connect the telencephalon with the hypothalamus/ventral midbrain, highlighting the existence of an early basic plan in the functional organization of the prosencephalic connectome.